Outcomes of laparoscopic appendectomy of a normally appearing appendix in children with suspected acute appendicitis: a tertiary care center experience - Wael Abosena; Mohamed Ahmed Elghazeery; Hisham Almohamady Almetaher; Ahmed Mostafa Aboelyazeed (BMC Pediatrics)
Abstract Background There is a lack of consensus among pediatric surgeons regarding the optimal management of a macroscopically normal appendix encountered during laparoscopy in children with suspected acute appendicitis. We hereby present our experience with laparoscopic appendectomy for macroscopically normal appendix in children with suspected acute appendicitis, evaluating its efficacy, safety, and postoperative histopathological findings of the excised specimens. Methods This retrospective study was conducted on 221 children with acute right lower quadrant abdominal (RLQA) pain and had a high clinical suspicion of acute appendicitis between January 2018 and January 2022. Among these, 38 patients were found to have a macroscopically normal appendix during surgery. All patients underwent appendectomy, and the excised specimens were sent for histopathological examination. Results Following laparoscopic appendectomy for macroscopically normal appendices in 38 children with suspected acute appendicitis, histopathological examination revealed pathological changes in 32 specimens (84%). Catarrhal appendicitis was identified in 26 cases (68%), fecalith obstruction in 5 cases (13%), and phlegmonous appendicitis in 1 case (3%), while only 6 specimens (16%) were histologically normal. The mean operative time was 51 min, with no conversions to open surgery. Postoperative complications occurred in 2 patients (5%), including one case of hyperpyrexia and one wound infection, both managed conservatively. The average hospital stay was 23.9 h, with 89% of patients discharged within 24 h. Postoperatively, all patients had complete RLQA pain resolution, with no complications or symptom recurrence during the three-month follow-up. Conclusion Our study supports appendectomy in pediatric patients undergoing laparoscopy for suspected acute appendicitis when no other pathology is identified, even if the appendix appears normal. This approach is justified with low morbidity, short hospital stays, symptom resolution without recurrence and only 16% of normal-looking appendices confirmed as histologically normal. However, larger multi-centre studies are needed to validate and standardize this practice.